Formulation, evaluation, and comparison of bilayered and multilayered mucoadhesive buccal devices of propranolol hydrochloride - Patel, Vishnu M. (Springer-Verlag, 2007)
The purpose of this research work was to establish mucoadhesive buccal devices of propranolol hydrochloride (PRH) in the forms of bilayered and multilayered tablets. The tablets were prepared using sodium carboxymethylcellulose (SCMC) and Carbopol-934 (CP) as bioadhesive polymers to impart mucoadhesion and ethyl cellulose (EC) to act as an impermeable backing layer. Buccal devices were evaluated by different parameters such as weight uniformity, content uniformity, thickness, hardness, surface pH, swelling index, ex vivo mucoadhesive strength, ex vivo mucoadhesion time, in vitro drug release, and in vitro drug permeation. As compared with bilayered tablets, multilayered tablets showed slow release rate of drug with improved ex vivo bioadhesive strength and enhanced ex vivo mucoadhesion time. The mechanism of drug release was found to be non-Fickian diffusion (value of n between 0.5 and 1.0) for both the buccal devices. The stability of drug in both the optimized buccal devices was tested for 6 hours in natural human saliva; both the buccal devices were found to be stable in natural human saliva. The present study concludes that mucoadhesive buccal devices of PRH can be a good way to bypass the extensive hepatic first-pass metabolism and to improve the bioavailability of PRH.